Overview of Antiepileptic Drug (AED) Use in Outpatient Patients at UNS Hospital - Maya Nur Ayu Fatdhillillah; Avianti Eka Dewi Aditya Purwaningsih; E. Aprilia L. Tobing (Jurnal FARMASIMED (JFM), 2026)
Epilepsy is a long-term disorder of the nervous system that requires long-term therapy using antiepileptic drugs (AEDs) to control seizures. The proper pattern of AED use plays a significant role in the effectiveness of treatment and patients’ overall well-being. This study aims to describe the use of antiepileptic drugs in outpatient patients at Universitas Sebelas Maret Hospital during the period of January-December 2024. This study used a non-experimental design with a descriptive approach, and data collection was conducted retrospectively through the review of medical records of epilepsy patients. From a total population of 1,236 medical record data, 303 samples were collected that satisfied the inclusion criteria. The analyzed data included patient characteristics based on gender and age, types of AED therapy, dosage, and usage rules. The study results show that outpatient epilepsy patients were predominantly female (53.14%) and the young adult age group 19-65 years (81.19%). The most commonly used therapy pattern was monotherapy, with Phenytoin 100 mg being the most frequently prescribed drug (28.38%), mainly at a dose of 1 tablet twice daily. Combination therapy was used in some patients with variations of two to four antiepileptic drugs. The conclusion of this study indicates that phenytoin is still the primary choice in the outpatient management of epilepsy at UNS Hospital, and reflects its role as a first-line drug effective in controlling various types of seizures. Predominated by females (53.14%) and the young adult age group aged 19-65 years (81.19%).